Team decision-making: the integration of cognitive task analysis and video to accelerate the development of tactical shared mental models in an elite sports team - Richards, P.; Robbins, M.; Collins, D. (Frontiers in Sports and Active Living, 2025)
Introduction: The focus of this article is on developing and operationalising shared mental models in elite sports teams, using a Decision-Making Framework.The Decision-making Framework innovatively integrates Cognitive Task Analysis (CTA) methods into off-field after action review meetings (AAR) to enhance on-field performance.